Potensi Tempurung Kelapa Sebagai Pembangkit Listrik Dengan Menggunakan Termoelektrik Generator - Sintiani Perdani; Didik Ari Wibowo; Desmira Desmira (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Around 35% of the total utilization of coconuts at this time is still not fully utilized. Thermoelectric is a technology that converts heat energy directly into electrical energy or converts electrical energy into heating and cooling energy. Data retrieval using two multimeters and an electric thermometer, data collection was carried out for 2 minutes. From the test results, this tool can produce an average voltage of 10.05 Volt for 200gram coconut shells, an average current of 0.99 Ampere and an average power of 13.84 Watts and can fully charge the battery up to 3 hours 33 minutes, while for 300 grams produces an average voltage of 10.59 Volts for 300gram coconut shells, an average current of 0.995 Ampere and an average power of 13.56 Watts and the battery can be fully charged in about 3 hours 36 minutes, while a coconut shell weighing 400 grams can produces an average voltage of 10.94 Volts, an average current of 1 Ampere and an average power of 13.70 Watts and the battery can be fully charged in about 3 hours 30 minutes. The more coconut shells used for combustion, the hotter the temperature and the faster the voltage and current are obtained, but with a note that the maximum temperature limit of the thermoelectric is T not more than 200o C. Keywords: Coconut Shell, Thermoelectric, Electrical Energy.